Economic Cities. - Sigler, Thomas; Searle, Glen; Martinus, Kirsten (Palgrave Macmillan, 2020)
The chapter explores the economy of cities in greater detail. First, it gives a summary of the growth and development of cities over time with respect to their economic function. One of the most important trends over the past century has been rapid urbanisation tied to industrialisation. In some parts of the world, there has been subsequent deindustrialisation. Next, the chapter focusses on the spatial implications of economic change in cities. As urban economies shift over time, so do the characteristics of the built environment, including employment nodes and residential housing. Suburbanisation driven by increasing car ownership has been an important process, but has occurred unevenly in different contexts. The chapter concludes by considering how cities have changed in the recent past, and how economic functions tied to the information age continue to transform cities and urban spatial structure.
Keywords: Stadtökonomie; Stadtwachstum; Industrialisierung; Deindustrialisierung; Suburbanisierung; Stadtbildveränderung; Wirtschaftsgeschichte; Stadtentwicklung